Level of sprint and jump abilities and intermittent endurance of elite young soccer players at different positions - Pivovarnicek, P.; Pupis, M.; Tonhauserova, Z.; Tokárová, M. (SportLogia, 2013)
The aim of the study was to analyse a level of sprint abilities, jump abilities and intermittent endurance of playing groups divided according to playing positions (goalkeepers, defenders, midfielders, forwards) from Slovak national under-21 soccer team (N=18, goalkeepers n=2, defenders n=4, midfielders n=7, forwards n=5) in time of qualification for the UEFA European Under-21 Football Championship 2011. The level of sprint abilities was diagnosed with the device Fitro Light Gates (FiTRONIC, Bratislava, The Slovak Republic). The criterion for the level assessment was the time obtained in the distance of 10m with the exactness of 0.01s. The level of jump abilities was diagnosed with the device FiTRO Jumper (FiTRONIC, Bratislava, The Slovak Republic). The criterion for the level assessment was the jump height in centimeter (cm) with the exactness of 0.1cm. Intermittent endurance was diagnosed with Yo-Yo Intermittent recovery test, level 2. The criterion for the evaluation was total overcame distance in the test in metres (m). Differences in the level of sprint abilities, jump abilities and intermittent endurance were recognised and defined with the special subject analysis. The level of sprint abilities of the whole group was presented with the average performance with the value 2.21±0.08 s, the level of jump abilities with the average performance with the value 39.0±4.2 cm and the level of intermittent endurance with the average value 1283±294 m, what means VO2max.kg-1= 62.7±4.0 ml.kg-1min-1. We have not found out with special subject analysis any significant differences in monitored parameters between groups divided according to playing positions. The significantly lower level was observed only in the level of sprint abilities and intermittent endurance of goalkeepers.